Association of cadmium, lead and mercury with paraoxonase 1 activity in women. - Anna Z Pollack; Lindsey Sjaarda; Katherine A Ahrens; Sunni L Mumford; Richard W Browne; Jean Wactawski-Wende; Enrique F Schisterman (PLoS ONE)
Background The activity of paraoxonase 1 (PON1), an antioxidant enzyme whose polymorphisms have been associated with cancer risk, may be associated with metals exposure. Objective To evaluate PON1 activity in relation to cadmium, lead, and mercury levels in healthy, premenopausal women. Methods Women from upstate New York were followed for ≥ two menstrual cycles. Repeated measures linear mixed models estimated the association between cadmium, lead, and mercury levels (by tertile: T1, T2, T3) and PON1 arylesterase (PON1A) and PON1 paraoxonase (PON1P) activity, separately. Analyses were stratified by PON1 Q192R phenotype and un-stratified. Results Median blood cadmium, lead, and mercury concentrations were 0.30 µg/L, 0.87 µg/dL, and 1.15 µg/L. In un-stratified analyses cadmium and mercury were associated with decreased PON1A activity (T2 vs. T1; not T3 vs. T1) but metals were not associated with PON1P. Phenotypes were distributed between QQ (n = 99), QR (n = 117), and RR (n = 34). Cadmium was associated with decreased PON1A activity for QR and RR phenotypes comparing T2 vs. T1 (-14.4% 95% confidence interval [CI] [-20.1, -8.4] and -27.9% [-39.5, -14.0],). Lead was associated with decreased PON1A (RR phenotype, T3 vs. T1 -18.9% [-32.5, -2.5]; T2 vs. T1 -19.6% [-32.4, -4.4]). Cadmium was associated with lower PON1P comparing T2 vs. T1 for the RR (-34.9% [-51.5, -12.5]) and QR phenotypes (-9.5% [-18.1, 0.0]) but not comparing T3 vs. T1. Cadmium was associated with increases in PON1P levels (QQ phenotype, T3 vs. T1 24.5% [7.0, 44.9]) and mercury was associated with increased PON1A levels (QQ phenotype, T3 vs. T1 6.2% [0.2, 12.6]). Mercury was associated with decreased PON1P (RR phenotype, T2 vs. T1 -22.8 [-37.8, -4.1]). Conclusion Blood metals were associated with PON1 activity and these effects varied by phenotype. However, there was not a linear dose-response and these findings await replication.